КАРТОПТЫ, ОРАМЖАПЫРАҚТЫ, СƏБІЗДІ САҚТАУ КЕЗІНДЕ МИКРООРГАНИЗМДЕРДІҢ ТҮРЛЕРІН АНЫҚТАУ (Experimental biology, 2017)
In given article are presented results on identifications of most constantly meeting microorganisms to stages of cultivation of vegetable cultures, in particular a potato, cabbage and carrots.
Keywords: potato; cabbage; carrots